Enforcement of the Code of Ethics of Judges as an Instrument of the Rule of Law: A Legal-Philosophical Analysis in Indonesia - Hariang Dede Taufik; Haerul Apandi; Andi Haruman; Haryanto Aritonang; Yeti Kurniati (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
The enforcement of the judge's code of ethics is an important element in realizing the rule of law because the integrity, independence, and impartiality of judges determine the legitimacy of the judicial institution. However, various cases of ethical violations, such as bribery practices, conflicts of interest, abuse of authority, and weak internal supervision show that the enforcement of the code of ethics of judges in Indonesia has not been running optimally. This condition has an impact on declining public trust in the judiciary and weakening the function of law as a means of realizing substantive justice. This study aims to analyze the position of the judge's code of ethics as an instrument of the rule of law, examine the effectiveness of its enforcement, and identify obstacles that affect its implementation in a legal-philosophical perspective. The research method used is normative legal research with legislative, conceptual, and philosophical approaches. Legal materials are obtained through literature studies of laws and regulations, scientific literature, and related documents, then analyzed qualitatively-prescriptively. The results of the study show that the weak enforcement of the judge's code of ethics is influenced by structural problems in the supervision system, legal culture that does not support professional integrity, and the inoptimal internalization of moral values in judicial practice. The enforcement of the code of ethics depends not only on regulations and supervisory mechanisms, but also on the professional virtues of judges which include integrity, honesty, responsibility, and moral courage. Therefore, strengthening the rule of law requires increasing the authority and effectiveness of ethical supervision, transparency in the handling and publication of ethical decisions, ongoing ethical education of judges, and synchronization between ethical norms and judicial disciplinary mechanisms to strengthen judicial integrity and public trust